Analisis Dampak Sosial Efek Bandwagon Pada Eksistensi Remaja: Studi di Kota Pekanbaru dan Kota Bukitinggi - Zatrahadi, M. Fahli; Darmawati, Darmawati; Rahmad, Rahmad; Syarifah, Syarifah; Arsy, Nur (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
Teenagers have a strong sense of their individual identity, interests, and personal desires and tend to be better able to defend themselves so as not to be affected by the bandwagon. The aim of this research is to analyze the social impact of the bandwagon effect on the existence of teenagers in Pekanbaru City and Bukitinggi City. The research method uses a qualitative approach. Nine informants came from the cities of Pekanbaru and Bukit Tinggi. Informants came from the Tourism, Youth, and Sports Agency, the Latah Tuah Studio, and the Titian Rang Mudo Art Studio. According to the research, there are many advantages for teenagers who actively support the preservation of Minang and Malay culture and are not subject to the harmful bandwagon effect. They have a deep understanding of their culture, strengthen their identity, contribute to cultural preservation, increase respect for other cultures, create communities and networks, and develop their skills and talents. They can strengthen their cultural heritage, develop a sense of pride and self-esteem, and promote intercultural tolerance and understanding.